PALYNOLOGIC AND LITHOSTRATIGRAPHIC RESEARCH OF LACUSTRINE, MARSH AND FLUVIAL QUATERNARY DEPOSITS IN RAŠICA DOLINA AND MIŠJA DOLINA, AND ON RADENSKO POLJE - Culiberg, Metka; Dozet, Stevo (Hacquetia, 2015)
The article deals with the results of palynological and stratigraphical research of lacustrine, marsh and fluvial Quaternary deposits in the Rašica dolina and Mišja dolina, and on Radensko polje. Correlation with equivalent Quaternary deposits and their palynoflora from the Grosuplje polje area was also performed. In the study area, Mesozoic, predominantly carbonate rocks are transgressively covered by Quaternary deposits which are in general composed of five lithostratigraphic units (from bottom to top): 1. gravel, 2. grey lacustrine clay, 3. reddish brown loam, 4. light grey marly clay and 5. alluvial marsh deposits. On the basis of pollen analysis the Quaternary sediments of the study area are chronostratigraphically classified to the Late or Middle Pleistocene and Holocene.